Determinants of Biogas Technology Adoption in Rural Households of Aleta Wondo District, Sidama Zone, Southern Ethiopia. (21st April 2021) - Geddafa, Tale; Melka, Yoseph; Sime, Getachew
Abstract : Biogas is environmentally sound and economically viable, clean, and renewable energy source. Despite its numerous benefits and dissemination efforts, the adoption of biogas technology has been low. The objective of this study was to assess factors determining adoption of biogas technology as an alternative energy source at household level in Aleta Wondo district, southern Ethiopia. A multistage sampling technique was employed to select sample households. A total of 148 sample households, 51 biogas technology adopters, and 97 nonadopter households were surveyed. The collected data were analyzed by inferential statistics and econometric model using STATA version 13.1. Results from the probit model showed that education level of household head, annual income level, livestock holding size, access to technical support, and level of awareness have significant positive influence on households' decision to adopt biogas technology. Other factors include poor performance of biogas plants associated to technical problems, and high installation costs unaffordable to the majority of rural population had a negative implication in adoption process. These are also the factors contributing to low adoption. Therefore, raising the population awareness on the benefits of biogas and assigning the biogas technicians who can give immediate maintenance services at "Kebele" level could extend the biogas technology.